2010
DOI: 10.1099/mic.0.036004-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic phototrophic nitrite oxidation by Thiocapsa sp. strain KS1 and Rhodopseudomonas sp. strain LQ17

Abstract: In anaerobic enrichment cultures for phototrophic nitrite-oxidizing bacteria from different freshwater sites, two different cell types, i.e. non-motile cocci and motile, rod-shaped bacteria, always outnumbered all other bacteria. Most-probable-number (MPN) dilution series with samples from two freshwater sites yielded only low numbers (¡3¾10 3 cm "3 ) of phototrophic nitrite oxidizers. Slightly higher numbers (about 10 4 cm "3 ) were found in activated sewage sludge. Anaerobic phototrophic oxidation of nitrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 47 publications
(38 reference statements)
1
37
0
2
Order By: Relevance
“…Recent research reported the ability of non-nitrifying bacteria related to the Rhodopseudomonas spp. (purple non-sulfur bacteria -strain LQ17) to use nitrite phototrophically as an electron donor as well (Schott et al, 2010). In addition, in our study, five of the remaining clone sequences (SNAD_16SrRNA_NOB(1_5, 2_5), SNAD_16SrRNA_NOB(1_6, 1_9, 2_2) and SNAD_16SrRNA_NOB_1_8) were closely related to Nitrobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research reported the ability of non-nitrifying bacteria related to the Rhodopseudomonas spp. (purple non-sulfur bacteria -strain LQ17) to use nitrite phototrophically as an electron donor as well (Schott et al, 2010). In addition, in our study, five of the remaining clone sequences (SNAD_16SrRNA_NOB(1_5, 2_5), SNAD_16SrRNA_NOB(1_6, 1_9, 2_2) and SNAD_16SrRNA_NOB_1_8) were closely related to Nitrobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis gained strong support from the recent isolation of extant phototrophic NOB in the genera Rhodopseudomonas and Thiocapsa , which are closely affiliated with Nitrobacter and Nitrococcus , respectively (Schott et al , 2010). The NXR of Nitrobacter and Nitrococcus is oriented toward the cytoplasm (see also above).…”
Section: Discussionmentioning
confidence: 98%
“…This hypothesis gains support from analyses of the genes upstream and downstream of nxr (Supplementary Text S1 and Supplementary Figures S4a, S4c and d). Whether this evolutionary scenario supports or contrasts a phototrophic origin of nitrite oxidation in Nitrobacter and Nitrococcus (Teske et al , 1994) is a fascinating question that might be better illuminated once first sequences of nxr loci from the proteobacterial phototrophic NOB (Schott et al , 2010) become available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these ICM resemble those of related phototrophic proteobacteria (purple bacteria), Teske et al (1994) hypothesized that Nitrobacter and Nitrococcus evolved from phototrophic ancestors where nitrite was used as electron donor for anoxygenic photosynthesis. Indeed, phototrophic nitrite oxidizers from the genera Rhodopseudomonas and Thiocapsa , which are closely related to Nitrobacter and Nitrococcus , were discovered recently (Schott et al, 2010). In contrast, Nitrospira lack ICM.…”
Section: Discussionmentioning
confidence: 99%